Phenotypic and Genotypic Antimicrobial Resistance Profile of Salmonella spp. Isolated from Kampung Chicken Carcasses - Nurjanah, Siti; Rahayu, Winiati P.; Sanjaya, Stephen (HAYATI Journal of Biosciences, 2024)
Kampung chicken meats have been widely consumed in Indonesia as well as broiler chicken. However, the extensive rearing allowed multidrug-resistant (MDR) bacteria exposure to kampung chicken, including through horizontal gene transfer. This study aimed to observe the correlation between the phenotypic and genotypic antimicrobial resistance profile of Salmonella spp. isolated from kampung chicken carcasses. Phenotypic antimicrobial resistance was evaluated by Kirby-Bauer's disk diffusion method, while the detection of drug resistance genes in seventeen isolates of Salmonella was carried out by PCR. All (17/17) isolates were susceptible to ampicillin and chloramphenicol. Most isolates of Salmonella were resistant to erythromycin (82%; 14/17), while the decreased susceptibility (intermediate category) most occurred in oxytetracycline (82%; 14/17). Salmonella Typhimurium showed a resistance pattern to more antimicrobial groups than S. Newport and S. Weltevreden. Several antimicrobial resistance genes (blaTEM, tetG, cmlA, gyrA) were present in all (17/17) isolates of Salmonella spp. Resistance to antimicrobial agents and the presence of resistance genes were not always related. This study could provide beneficial information regarding the transmission of antimicrobial resistance among Salmonella spp. from kampung chickens.